2023
DOI: 10.4314/bcse.v37i5.20
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the corrosion inhibition of magnesium by coatings formulated with nano CeO and ZrO particles

V. K. Neela Murali,
M. S. Starvin,
J. Bensam Raj

Abstract: ABSTRACT. In this study, zirconium oxide (ZrO)-cerium oxide (CeO) based composite coatings were fabricated using doctor blade method to protect pure magnesium from corrosion. The effects of ZrO and CeO on corrosion resistance of magnesium coatings were investigated using Tafel polarization method. Uniform deposition of composite coating without micro-voids was observed from scanning electron microscopy (SEM) analysis. The results exhibit that the addition of CeO show a higher corrosion resistance in comparison… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Haewon Byeon et al [33] creates innovative and efficient techniques to prevent corrosion and protect materials in the food, Corrosion and inhibition studies on AISI 316 with AISI 410 fiber laser welded joints automotive, and large-scale energy sectors. Neela Murali et al [34] revealed the inhibition of magnesium coated by CeO and ZrO particles Out of three corrosion mediums, the acid medium exposed the highest weight loss. Hence, this work initiated to propose the control method for the welded joints using organic solid inhibitors.…”
Section: Microstructure Analysismentioning
confidence: 99%
“…Haewon Byeon et al [33] creates innovative and efficient techniques to prevent corrosion and protect materials in the food, Corrosion and inhibition studies on AISI 316 with AISI 410 fiber laser welded joints automotive, and large-scale energy sectors. Neela Murali et al [34] revealed the inhibition of magnesium coated by CeO and ZrO particles Out of three corrosion mediums, the acid medium exposed the highest weight loss. Hence, this work initiated to propose the control method for the welded joints using organic solid inhibitors.…”
Section: Microstructure Analysismentioning
confidence: 99%
“…iron corrosion in concentrated acidic aqueous solutions is a major concern in the most of industries where acids are commonly employed for many applications such as acid cleaning, acid descaling, acid pickling, and oil well acidizing, because of the acid solution's general abrasiveness, construction materials corrode quickly, to prevent metal breakdown and reduce acid usage, corrosion inhibitors must be added [8]. The use of nanotechnology to change the iron/electrolyte contact has been used to lessen the impact of corrosive conditions (e.g production of nanocomposite coatings on Stainless steel) [9][10][11]. The use of nanomaterials for corrosion control has made significant progress recently, as summarized in [12].…”
Section: Introductionmentioning
confidence: 99%